MORAL VALUES OF THE MAIN CHARACTER IN THE FILM ENOLA HOLMES AND ITS CONTRIBUTION TO CHARACTER BUILDING - Yusriyah, Satiti (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2022)
Learning media can convey lesson information to students and stimulate their thoughts, feelings, attention, and willingness, and it can encourage the learning process. The film presents various stories that contain the moral values ​of life. One of the films to choose from is Enola Holmes. Enola Holmes is a film released in 2020 adaptation of the Nancy Springer book series The Enola Holmes Mysteries. Enola Holmes is directed by Harry Bradbeer and written by Jack Thorne. This study aimed to determine the moral values ​​represented by the main character in the film Enola Holmes for character building in students. This study uses the formulation of Kemendikbud (2017). The data collection method is the documentation research method and the technique of collecting data from Miles & Huberman (1994). Researchers used descriptive qualitative research. The subject of this study used subtitles in the film Enola Holmes. The findings of the study there are five moral values with eight sub-values ​​of moral values ​​in the Enola Holmes film. From the result, the writer can conclude that nationalist (self-sacrifice) is the most dominant moral value in Enola Holmes’ film.